2013
DOI: 10.4028/www.scientific.net/amr.846-847.199
|View full text |Cite
|
Sign up to set email alerts
|

Voltage Stability Analysis of Islanded Microgrid

Abstract: The clean and renewable distributed generations (DGs) could be combined in microgrid. Keeping microgrid bus voltage stable is very important. This paper proposes an integrated control strategy of combining droop control and V/f control. A complementary wind-solar-energy storage microgrid model is built based-on Simulink software. The effect on voltage stability based on the integrated control strategy is analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…This algorithm fits the G(x)-λ with a polynomial function. Through mass numerical experiments [1], it is found that the parabolic approximation can guarantee both relatively high accuracy and efficiency. The parabolic function can be expressed as P(λ) = a(λb) 2 + c, where a, b, and c are constant coefficients.…”
Section: ) General Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…This algorithm fits the G(x)-λ with a polynomial function. Through mass numerical experiments [1], it is found that the parabolic approximation can guarantee both relatively high accuracy and efficiency. The parabolic function can be expressed as P(λ) = a(λb) 2 + c, where a, b, and c are constant coefficients.…”
Section: ) General Theorymentioning
confidence: 99%
“…It bases on the frequency variation of microgrid systems and avoids the frequent comparison of the voltage amplitudes in different nodes. The step control equation in [1] is shown as…”
Section: B Adaptive Step Size Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Ranges from 0.25 to 0 (No load to collapse point) [82] Sensitivity matrix Linearized load flow equation Static…”
Section: System-variable-based Vsismentioning
confidence: 99%